2021
DOI: 10.1111/and.14298
|View full text |Cite
|
Sign up to set email alerts
|

Using microRNAs as molecular biomarkers for the evaluation of male infertility

Abstract: Infertility is a multiplex disorder in the reproductive system, and men are responsible for more than half of the cases. Nowadays, semen analysis has been considered the critical assessment test to diagnose infertile men; however, it has limitations so that the cause behind infertility in 40% of infertile men is unrevealed. Weaknesses of semen assessment indicate a global need for novel and better diagnostic tools and biomarkers. MicroRNAs are short (about 18–22 nucleotide length) non‐coding RNAs that control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Some miRNAs have specific expression patterns inside the testis, either in different somatic cell types or in germ cells [ 21 ]. The presence of miRNAs in mature spermatozoa and seminal plasma and the alterations in their expression profiles in patients with spermatogenic problems demonstrate their potential as biomarkers for diagnosis and classification of male fertility [ 65 , 66 , 67 ]. These molecules represent a tiny function within the total RNA from samples, which can vary significantly across samples, so its normalization in RT-PCR analyses represents a massive challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Some miRNAs have specific expression patterns inside the testis, either in different somatic cell types or in germ cells [ 21 ]. The presence of miRNAs in mature spermatozoa and seminal plasma and the alterations in their expression profiles in patients with spermatogenic problems demonstrate their potential as biomarkers for diagnosis and classification of male fertility [ 65 , 66 , 67 ]. These molecules represent a tiny function within the total RNA from samples, which can vary significantly across samples, so its normalization in RT-PCR analyses represents a massive challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why each differentiating cell type has its own transcriptome profile [ 30 ]. Several studies have highlighted the role of small RNAs (siRNAs, piRNAs, miRNAs) in spermatogenesis and, therefore, in male fertility (reviewed in [ 6 , 17 , 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]). In particular, studies have shown that miRNAs can be expressed exclusively or preferentially in the testis and in specific testicular cell types, as shown by Gan et al, who found miRNAs to be more abundant in spermatogonia than in other testis cell types [ 34 , 39 , 40 , 41 ].…”
Section: The Role Of Mirnas In Spermatogenesismentioning
confidence: 99%
“…Fertility-related issues can lead to alterations in the expression profile of miRNAs, and this dysregulation may be a contributing factor to infertility [ 37 ]. Several studies have reported altered miRNA expression profiles with an infertility phenotype, and, therefore, miRNAs could have the potential to serve as diagnostic biomarkers (reviewed in [ 36 , 37 , 38 , 89 ]). Table 2 summarizes a number of studies that demonstrate the link between miRNA profile and impaired fertility.…”
Section: Mirnas In Male Infertility and Their Use As Biomarkersmentioning
confidence: 99%
“…Spermatogenesis is a complex process that can be divided into 3 stages: 1) mitosis, 2) meiosis and 3) spermiogenesis ( 19 ). Defects in this process may lead to the occurrence of NOA, which is one of the causes of male infertility.…”
Section: Sncrnamentioning
confidence: 99%